Penggunaan Model Pembelajaran Project Base Learning Untuk Meningkatkan Kreativitas Siswa SD - Tafhim Nur Falah; Winda Pujiyanti; Tiara Dwi Damayanti (Indonesian Journal of Elementary and Childhood Education, 2023)
Natural Sciences (IPA) does not only study concepts, but in science we can learn a process and mastery of scientific attitudes.  In fact, learning activities are still centered on educators, so students cannot develop knowledge and skills in thinking.  The knowledge and thinking skills possessed by students can experience significant changes, the way that can be done is by applying the Project Based Learning (PjBL) model in learning activities.  The Project Based Learning (PjBL) learning model is a learning model whose teaching and learning activities are project-based.  In every activity carried out students will get direct experience which can later increase creativity and student learning outcomes.  This study aims to determine the effect of using the Project Based Learning learning model on the creativity of fifth grade students of SD Negeri 1 Cangkreplor on the water cycle material.  This research uses a descriptive approach.  In this descriptive approach, researchers examine phenomena or populations that can be obtained from subjects in the form of individuals or organizations.  The implementation of Project Based Learning (PjBL) can be applied by way of educators explaining the process of the water cycle cycle, then students get projects in groups about the water cycle process, then students present their projects in front of the class.